The Effectiveness of Nueng Na Thong Aamong Students of the Faculty of Thai Traditional and Alternative Medicine, Ubon Ratchathani Rajabhat University: Phanida Kamuttachat - Kamuttachat, Phanida; Thiantongin, Pitchanan; Nusawat, Suphannachat (Princess of Naradhiwas University Journal, 2024)
The objective was to study reductions in waist circumference, belly fat level and body weight. Nueng Na Thong is the Thai health care wisdom. This was quasi-experimental research with 35 subjects. The research tools consisted of the questionnaire and experimental record form. The reliability was tested by Cronbach method, resulting in the value equal to 0.83. Statistics used for data analysis were number, percentage, mean, standard deviation, Pearson correlation coefficient analysis and multiple regression analysis. The results showed that the experimental group had post-test waist circumference, belly fat level and body weight with statistically significant difference at 0.05level with a 2.39 cm reduction in waist circumference, a 0.51 cm reduction in post-test belly fat level and a 0.03 kg reduction in body weight. The degree of heat sensation highly affected in the same direction as waist circumference (r = 0.741) in a statistically significant manner at 0.05 level and the degree of heat sensation affected waist circumference, belly fat level and body weight. Daily life behavior was a mediator variable in a statistically significant way at 0.05 level and the ability to explain the relationship was 33.40, 37.70 and 37.00 percent. Abdominal for reducing body composition (Nueng Na Thong) had moderate heat sensation, tolerance ( = 5.79 S.D. = 0.21). No side effects were found. Overall daily life behavior was at occasional level ( = 2.49 S.D. = 0.18). Eating, best practices were practiced at frequent level ( = 3.07 S.D. = 0.34). The experiment resulted in reduced waist circumference, belly fat level and body weight. In this regard, daily life behavior must be jointly controlled as well.